PENDEKATAN S-C-P PADA PENGUKURAN EFISIENSI PEMASARAN BAWANG MERAH DI KABUPATEN PROBOLINGGO - Dyanasari Dyanasari; Wahyunindyawati Wahyunindyawati; Asnah Asnah; F. Kasijadi (BUANA SAINS, 2010)
This research aims to analyze structure, conduct and performance of marketing of onion at Probolinggo to measure market efficiency. Data analysis use structure, conduct, performance approach and regression methods. The analysis of market structure showed that market structure of onions moving between olygopsoni to perfect competition market, and there are not entry/exit barriers for new comer and so does no differentiation of product. Based on Kr, IH, CR4 and market share indicator, no one of traders can monopolize the market. Commodity flow analysis shows there at least eight kinds of marketing channels to distribute product from farmers to consumers. Market conduct analysis shows that pricing process based on individual negotiations no formal institution to control the market and no significant competition among traders. Market performance analysis shows that marketing cost, margin and marketing profit varies among traders and channels. Share of price of farmer relatively high. Price change of consumers transmitted to price change of producers correctly, producers market and consumers market has been integrated with reference market. According to market structure, conduct and market performance, we saw the marketing system not yet efficient